Serum vitamin D insufficiency is correlated with quadriceps neuromuscular functions in patients with anterior cruciate ligament injury: A preliminary study - Jihong Qiu; Chi-Yin Choi; Gene Chi-Wai Man; Xin He; Mingqian Yu; Mingde Cao; Qianwen Wang; Jonathan Patrick Ng; Patrick Shu-Hang Yung; Michael Tim-Yun Ong (Elsevier, 2024)
Background: This study aimed to investigate the correlations of serum vitamin D insufficiency with quadriceps neuromuscular function in patients with anterior cruciate ligament (ACL) injury. Methods: A cross-sectional study was conducted. Eighteen patients with a primary, unilateral ACL injury who had insufficient serum vitamin D concentrations (<30 ng/ml) were recruited for the study. Bilateral quadriceps neuromuscular function, including maximal strength, the speed of rapid contraction, and inhibition, were measured on an isokinetic dynamometer with the hip and the knee joint flexion at 90° and 45°, respectively. Quadriceps strength was measured by maximal voluntary isometric contractions (MVIC); the speed of rapid contraction was quantified by the rate of torque development (RTD), which was divided into the early (RTD0-50) and the late phase (RTD100-200); quadriceps inhibition was quantified by the central activation ratio (CAR). Serum vitamin D concentration was quantitatively determined by serum 25(OH)D concentration measured by the 25(OH)D ELISA kit. The Spearman rank correlation analysis was used to examine the correlation between the vitamin D concentration and bilateral quadriceps MVIC, RTD0-50, RTD100-200, and CAR, respectively. Results: The results of Spearman rank correlation analyses showed that the serum 25(OH)D concentration was significantly correlated with bilateral quadriceps MVIC (injured: r = 0.574, p = 0.013; uninjured: r = 0.650, p = 0.003) and RTD0-50 (r = 0.651, p = 0.003), and CAR (r = 0.662, p = 0.003) on the uninjured limb. However, no significant correlations were found between the serum 25(OH)D concentration and the other outcomes. Conclusions: The serum vitamin D concentration correlates with quadriceps neuromuscular function in patients with ACL injury who had vitamin D insufficiency.